Música, dansa i espectacles medievals al Llibre de memòries de la ciutat de València. - MARCH, ROBERT (Scripta)
In this article we have commented on different medieval representations and festivities, as they appear in the Llibre de memòries de la ciutat de València, first edited by Carreres Zacarés (1935), and more recently by Escartí and Ribera (2019). We have paid attention to the different annotations with which notaries and chroniclers recorded some paratheatrical elements and, even, the processions, in addition to other events, such as, mainly, the royal entrances or, even, the presence of references to the sound and musical space.